The exercise of the voice: teaching proposal for education professionals (Review) (REDEL. Revista Granmense de Desarrollo Local, 2023)
For the education professional, the use of the voice in the teaching activity constitutes a challenge; since it becomes a model and linguistic reference for the learning of its students. Educators are communicators par excellence and it is important, taking into account the time in which they carry out their work activity, the development of an adequate vocal education. This paper addresses a problem related to insufficiencies in voice training that limit vocal education in these professionals. For this reason, the aim is to share experiences related to this topic. Theoretical (analytical-synthetic and inductive-deductive) and empirical methods (document analysis and observation) were used. Some of the techniques that can be applied for the practice of voice training and the design of teaching activities for the training of education professionals are included in the work.
Keywords: vocal education; voice training; teaching-learning process; professional training